Faktor Produksi Minyak Kelapa pada Industri Rumah Tangga di Desa Mekkatta Selatan, Majene - Akbar, Akbar; Azmi, Nur; Husain, Nailah (Universitas Muhammadiyah Kotabumi, 2025)
Indonesia is known as one of the countries with very abundant biodiversity, such as coconut users with a myriad of significant health benefits and applications. One of the most common processed coconut products is coconut oil. Coconut oil as one of the products of the home industry, has great potential in South Mekkatta Village, Majene Regency. Various factors can affect coconut oil production, ranging from internal factors such as the quality of raw materials and labor skills to external factors. This study aims to analyze the influence of factors affecting coconut oil production in the household industry in South Mekkatta Village, Malunda District, Majene Regency. This type of research is quantitative research. The method of determining the research sample using Simple Random Sampling, with a sample size of 39 people. The data analysis technique used is multiple linear regression analysis. The results showed that the amount of raw materials had a significant effect on coconut oil production, while labor, fermentation time, and production costs had no significant effect on coconut oil production.